A rotating rod electrode disk as an alternative to the rotating disk electrode for medium-temperature electrolytes, Part II: An example of the application in an investigation of the oxygen reduction reaction on a Pt/C catalyst by the thin film method in hot concentrated H3PO4. (10th August 2017) - Prokop, M.; Carda, M.; Bystron, T.; Paidar, M.; Bouzek, K.
Graphical abstract: Highlights: Rotating rod electrode (RRE) disk applied in 99% H3 PO4 at 160 °C. Thin-film method used to activate glassy carbon RRE disk as an electrode. Polybenzimidazole as a thin-film binder allowed to use electrode in hot H3 PO4 . O2 diffusion coefficient and ORR kinetics at Pt/C catalyst determined in hot H3 PO4 . Abstract: In this paper a novel and simple method to determine the O2 reduction reaction activity of Pt/C in 99% H3 PO4 at a temperature of 160 °C using a well-established thin film procedure is reported. It utilizes a disk of rotating rod made of glassy carbon as a working hydrodynamic electrode. By introducing polybenzimidazole as a thin film polymer binder, a modified rotating rod electrode disk (the cylindrical part is electrochemically inactive under the conditions used) suitable for measurements in hot concentrated H3 PO4 was obtained. Using this electrode together with the Koutecky-Levich equation modified for rotating rod electrode hydrodynamics, the kinetics of the oxygen reduction reaction and mass transfer parameters of O2 in 99% H3 PO4 at 160 °C were successfully determined. The presented method can be easily used to determine the activity of various catalysts under conditions which preclude the use of a conventional rotating disk electrode.